2015
DOI: 10.1111/apha.12467
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic signalling in the immune system

Abstract: The GABAergic system is the main inhibitory neurotransmitter system in the central nervous system (CNS) of vertebrates. Signalling of the transmitter γ-aminobutyric acid (GABA) via GABA type A receptor channels or G-protein-coupled type B receptors is implicated in multiple CNS functions. Recent findings have implicated the GABAergic system in immune cell functions, inflammatory conditions and diseases in peripheral tissues. Interestingly, the specific effects may vary between immune cell types, with stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
90
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 72 publications
4
90
0
3
Order By: Relevance
“…There are also examples of pLGICs with well-characterized roles in the nervous system that appear to function in non-neuronal tissues. For example, the mammalian immune system is rich in pLGICs, including nicotinic acetylcholine (nACh), GABA A and glycine receptors (Barragan et al, 2015;Borovikova et al, 2000;Dionisio et al, 2011;Froh et al, 2002;Prud'homme et al, 2015;Rosas-Ballina et al, 2011;Tracey, 2002). While such non-neuronal roles of the GABA and glycine receptors are poorly understood, the α7 nicotinic acetylcholine receptor (nAChR) is expressed in macrophages where it regulates tumour necrosis factor-α in response to acetylcholine released from spleen lymphocytes (Rosas-Ballina et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are also examples of pLGICs with well-characterized roles in the nervous system that appear to function in non-neuronal tissues. For example, the mammalian immune system is rich in pLGICs, including nicotinic acetylcholine (nACh), GABA A and glycine receptors (Barragan et al, 2015;Borovikova et al, 2000;Dionisio et al, 2011;Froh et al, 2002;Prud'homme et al, 2015;Rosas-Ballina et al, 2011;Tracey, 2002). While such non-neuronal roles of the GABA and glycine receptors are poorly understood, the α7 nicotinic acetylcholine receptor (nAChR) is expressed in macrophages where it regulates tumour necrosis factor-α in response to acetylcholine released from spleen lymphocytes (Rosas-Ballina et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The oxysterol receptor EBI2 (encoded by Gpr183) was previously shown to guide B cells during the germinal center reaction and to promote follicular T helper cell differentiation (45,46). With respect to Gabbr1, various studies suggested immunomodulatory functions of GABA, but the inhibitory effect of GABA on T cells was, so far, mainly attributed to the GABA A receptor subtype, a ligand-gated ion channel (47)(48)(49). The upregulation of Gabbr1 in CD4sc indicates that GABA B may also contribute to these effects, suggesting that GABA B agonist baclofen might have beneficial effects in MS treatment beyond management of spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…GABA activates GABA A receptors, which are ion channels, and GABA B receptors, which are G-protein-coupled receptors [128]. It is the main neurotransmitter with inhibiting effect in the CNS, regulating dopaminergic activity and playing a key role in the reduction of neuronal excitability throughout the nervous system.…”
Section: The Importance Of Dopamine and Other Neurotransmittersmentioning
confidence: 99%
“…It has been reported that T. gondii infection is followed by an increase in the motility and migratory capacity of infected dendritic cells, permitting propagation of the parasite to different tissues, including the brain [128]. Although dendritic cells are considered guardians of the immune system, they can also, paradoxically, mediate in the spread of the parasite.…”
Section: The Importance Of Dopamine and Other Neurotransmittersmentioning
confidence: 99%